Surgical Residents’ Perceptions Of The Operating Room Educational Environment And Associated Factors In The Surgical Department - Alhrbi, Ahmed Guddian M; Dinna, Abdulsttar Abdulrhman; Yaseen, Hasan Mohammed; alabbasi, Alhanouf fahad; Alkhowaitry, Seham Ali; almokati, Manea Sanhat; Alhindi, Majed Abdullah; Kalantan, Maher Yousof; Alzahrani, Nawaf Mosaed Ahmad; Alshehri, Abdullah Dhafer; Alnasiri, Khalaf Abed Abdullah (Migration Letters, 2022)
Background: The educational experience in operating rooms (OR) plays a central role in the transformation of a trainee into a surgeon. The educational environment refers to the "climate" that influences all aspects of learning in an educational context and the experience in the operating room is particularly crucial in surgical residents learning. The study aims: To assess surgical residents’ perceptions of the operating theatre educational environment and associated factors in the surgical department at King Fahad General Hospital in Jeddah. Methods: A cross-sectional study was conducted from January to March 2022 among surgical residents to assess their perceptions of the operating room educational environment using the OREEM questionnaire. Descriptive statistics (mean, median, SD) were used to summarize demographic data and OREEM scores. The student t-test and one-way analysis of variance (ANOVA) testing followed by posthoc tests were used for comparison of quantitative data, with p-values < 0.05 considered significant. Results: Of the participants, 103 (79.8%) were male and 26 (20.2%) were female with a mean age of 28 years. The overall mean score was 69% with subscale scores for teaching and training at 47.9/65.0 (73.7%), lear[1]ning opportunities at 34.5/55.0 (62.7%), the atmosphere at 28.9/40.00 (72.4%) and workload/supervision/ support at 27.5/40.0 (68.7%). Male and female residents differed significantly in perceptions of "atmosphere" (t127 = 3.35, p < 0.001) and in junior versus senior residents’ perceptions of the “learning opportunities” and “atmosphere” at p-values of 0.023 and 0.028 respectively. However, age, marital status, and specific surgical training programs did not have a significant effect on the scores. Conclusion: Overall, residents had positive perceptions of their training and teaching, learning opportunities, the atmosphere in the operation theatre, and the supervision they received in the operation theatre. The operating room’s "teaching and training" component received the highest score, while the operating room’s "learning opportunities" component received the lowest. This indicates the importance of establishing a positive learning environment with sufficient "hands-on" experience, especially during emergencies. In addition, preoperative planning, case discussions, and feedback after the surgery should be routine.